Analisis Pengukuran Kinerja Menggunakan Metode Balanced Scorecard pada PT.Bahtera Utama - Erwin Erwin; Hartiwi Prabowo (Bina Nusantara University, 2015)
This research was conducted in PT.Bahtera Utama by measuring performance using the Balanced Scorecard as measured through four perspectives, that is financial perspective, the customer perspective, internal business process perspective, and learning and growth perspective. The purpose of this study was to measure the performance with balanced scorecard, analyze and recommend the results to the company. The research method used is a case study and survei methods with descriptive research. The results of this study indicate that the performance of the financial perspective quite good includes the profits, revenue, productivity, and the short term liabilities have not been able to be achieved as expectations. For Customer perspective, the performance of the companies is very good where customer satisfaction and loyalty must be maintained, for the continuation of the order. For Internal Business Process perspective, the company's performance in terms of both innovation and quality of products are very good, but in the time of processing product distribution is average and company has been able to fix it with the strategic objectives effectively and efficiently. For learning and growth perspective, the performance is good at all points but in the employee productivity and commitment, the targets have not been able to be achieved and the application of the information technology is very good. Overall assessment of performance on the PT.Bahtera Utama is good with the score of 4.29.